Maximizing donor allocation: A review of UNOS region 9 donor heart turn‐downs. Issue 12 (5th October 2017) - Mancini, Donna; Goldstein, Daniel; Taylor, Samantha; Chen, Leway; Gass, Alan; DeLair, Samantha; Pinney, Sean
Abstract : This study was performed to determine if organ selection practices for heart utilization by Region 9 transplant programs were optimal, and to identify opportunities to increase local organ recovery. A retrospective review of de‐identified region‐wide donor data January 1, 2010 through December 31, 2013 was performed. Over the study period 537 heart donors were identified, of which 321 (60%) were transplanted. Two hundred‐sixteen consented hearts were not used; 190 of these were not recovered, and 26 were recovered but not transplanted. Of these, 245/321 (76%) hearts were transplanted at one of 5 regional programs, 15 (5%) were transplanted out of region as primary offers, and 61 (19%) were turned down in region and exported. Of the 61 exported hearts, 43 were turned down in region for donor‐related "quality" codes (UNOS 830, 833‐837) by at least one program, the remaining 18 hearts were turned down for non‐"quality" reasons, primarily histocompatibility and size. Only 5/43 exported were turned down for "quality" reasons by all regional programs offered the organ. A review of consented, not recovered donor offers suggested an additional 28 organs were possibly appropriate for transplant. Our review of regional turn‐downs suggests transplant centers could potentially identify additional usable organs without compromising short‐term outcomes. Abstract : This retrospective study evaluates the organ selection practices in UNOS region 9 to optimize donor utilization, and suggests that additional usable organs with good short‐term outcomes can be identified.